2020
DOI: 10.1108/ajim-04-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model to identify the antecedents and consequences of user satisfaction with digital libraries

Abstract: PurposeThe primary objective of the present study was to design and develop a model to identify the antecedents and consequences of user satisfaction with digital libraries.Design/methodology/approachThe theoretical framework of this study was based on information system success theory, technology acceptance model (TAM), media affinity theory, satisfaction-loyalty theory and engagement theory. In so doing, eight hypothesized relationships were formulated to develop the conceptual model. The study approach was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Apparently, according to Soltani-Nejad et al. ’s study (2020), it can be logically inferred that the DHP-LCLW with HTAT composed of Mr. Lo Chia-Lun’s writings database and the developed digital humanities tools also has good system quality, service quality and information quality to some degree.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Apparently, according to Soltani-Nejad et al. ’s study (2020), it can be logically inferred that the DHP-LCLW with HTAT composed of Mr. Lo Chia-Lun’s writings database and the developed digital humanities tools also has good system quality, service quality and information quality to some degree.…”
Section: Discussionmentioning
confidence: 98%
“…Soltani-Nejad et al. ’s study (2020) indicated that system quality, service quality and information quality of digital libraries are important factors affecting the formation of perceived usefulness and perceived ease of use in technology acceptance. Apparently, according to Soltani-Nejad et al.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the topic, despite the considerable attention that digital libraries have received in the literature, (i.e., Afthanorhan et al, 2020 ; Bilal & Bachir, 2007 ; Soltani-Nejad et al, 2020 ; Thong et al, 2002 ; Xu & Du, 2018 ) a minimal amount of research has been conducted regarding the EKB, and these researches were strictly conducted from the perspective of librarianship (i.e., Eldakar & Kenawy, 2020 ; Mansour, 2020 ). Thus, to advance research and practice in this domain, researchers have to address and explore the success of the EKB with respect to the revolution of virtual education which evolved due to the spread of the coronavirus pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Soltani-Nejad et al [4] showed that the generic usability of the quality of digital resources could even be used as a functional theoretical framework to predict and understand the factors contributing to user satisfaction in the domain of digital library. The importance of this issue is due to the fact that today’s society is an information- and knowledge-based society, and this characteristic has led organisations and organisational models to continually move towards knowledge-based organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the production of valuable content with the purpose of marketing information goods and services in libraries and information centres has become increasingly important, as libraries view this digital content as users' new information needs. Besides making it possible to adapt content to their users' needs in libraries, new technologies and networking environments make content accessible through their websites or social networks, or internet content providers such as Blinkist, 3 Google Podcasts, 4 OverCast, 5 Castbox 6 and BPluspodcast. 7 They also market their products to a wider range of users and can attract their attention more.…”
Section: Introductionmentioning
confidence: 99%